Adsorption kinetics and equilibrium of methylene blue from aqueous solutions using phosphoric acid treated date seeds / Tengku Nur Liyana Tengku Zainul Hisham - Tengku Zainul Hisham, Tengku Nur Liyana (Faculty Of Applied Sciences, 2016)
In this study, the adsorbent material used to adsorb methylene blue from aqueous solutions is phosphoric acid treated date seeds. Agricultural wastes are selected as adsorbent due to their low cost compared to high cost adsorbent such as activated carbon. Parameters examined in this study are agitation rate, pH, adsorbent dosage, temperature, contact time and initial concentrations. For kinetic study, pseudo-first --order and pseudo-second-order are used to analyze the adsorption rate of methylene blue on date seeds.